The assessment of the impact of socio-economic factors in accepting cancer using the Acceptance of Illness Scale (AIS) - Czerw, Aleksandra; Bilińska, Magdalena; Deptała, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : The paper presents the results of examining the level of acceptance of the illness in cancer patients using the Acceptance of Illness Scale (AIS). Materials and methods: The study involved cancer patients treated at the Central Clinical Hospital of the Ministry the Interior in Warsaw in 2014. The questionnaire comprised basic demographic questions (socio-economic factors) and the AIS test estimating the level of illness acceptance in patients. Results : For the group of patients in the research group, the arithmetic mean amounted to 27.56 points. The period of time that elapsed between the first cancer diagnosis and the start of the study did not influence the score of accepting illness. The acceptance of illness in patients diagnosed with metastases differed from the acceptance of illness by patients diagnosed with metastatic cancer. Females obtained the average of 29.59 in the AIS test, whereas the average in male patients was 26.17. The patients’ age did not impact the AIS test. There were no differences in the AIS test results between a group of people with secondary education and a group of people with higher education. There were no differences in the AIS test results between employed individuals versus pensioners. The inhabitants of cities were characterized by the highest degree of acceptance of their health condition. The lowest degree of acceptance of illness was observed in the group with the lowest average incomes. In the group of married individuals the average degree of acceptance of illness amounted to 27.37 points. The average degree of acceptance of illness in patients that declared themselves as single amounted to 25.75. Conclusions : The average degree of acceptance of illness in the study group was 27.56 points, which is a relatively high level of acceptance of cancer. The main socio-economic factor, which influenced the AIS test results was whether metastases were diagnosed or not. There were no differences between patients in groups where the time that elapsed from the first diagnosis of cancer varied. There were no statistical differences between female and male patients as well as patients of different age. Additionally, the level of education and patients’ professional status did not impact in the AIS test results.